Development of the Citizenship Education Method in Fostering Digital Citizenship Through Information and Communication Technology in Schools - Kartini, Dedeh; Dewi, Sri Anggraini Kusuma (GoAcademica Research & Publishing, 2024)
The presence of information technology generally has a fairly high positive impact on society. This can help facilitate various community activities. However, unfortunately, there is a lot of misuse of this technology, so as a result there is a need to learn the norms for using technology, especially among students. This research then aims to look at strategies for developing PKN methods so that they can foster digital citizenship by utilizing information and communication technology in schools. This research will be carried out using a qualitative approach. The population used in this research was class XI students at Rawamerta State Vocational School. The results of this research then found that increasing understanding of the concept of digital citizenship can be stimulated through the preparation of Citizenship Education materials that attract students' interest. The attraction of a topic will be an incentive for students to be more active in learning, especially when the material is integrated into the context of everyday life. Contextual digital citizenship material can be presented in the form of concrete experiences, making it easier for students to understand the learning content. Thus, the development of digital citizenship can be successful through this approach.